Database Support For Planning Agricultural Development Programmes At The Grass Roots Level - O. R SULAJA AND JIJU P. ALEX (Journal of Global Communication, 2016)
Micro level planning practiced by local bodies in Kerala has been found to have nine distinct stages viz. situation analysis and resource appraisal by working groups, citizen consultation through village council, projectisation by working groups, consolidation of project ideas, plan finalization, approval by expert committees, administrative sanction by District Planning Committee, implementation by accredited agencies and participatory monitoring and evaluation (Government of Kerala, 2012). Each stage requires diverse data and information from different levels for effective decision making. The sources of information employed in different stages shall be classified into legacy databases, secondary sources, and on line/ offline digital sources. Legacy databases which are traditional registers and records are the main sources of data for planning. Secondary sources and digitized sources are fewer in number. A study conducted in the Grama Panchayaths of Kerala showed the extent of use of databases in micro level planning, their sources and status of availability. Though 85 per cent of the data required for micro level planning are available from various legacy and secondary sources, 55 per cent of this data are only partially used. Major constraints in availing data support in micro level planning are lack of databases in usable form, lack of free access, lack of facilities for digitization etc. As micro level planning is gaining importance, the data support at the local level has to be enhanced by updating, digitizing the existing ones and creating new databases. Efforts to create location specific databases through participatory tools also need to be encouraged. Effective micro level planning necessitates development of an integrated information system that can be easily accessed.